ENTHALPY OF FORMATION OF CASI2O5, A QUENCHED HIGH-PRESSURE PHASE WITH PENTACOORDINATE SILICON - Schoenitz M.; Navrotsky A.; Ross N. (My University, 2001)
The monoclinic titanite-like high-pressure form of calcium disilicate has been synthesized and quenched to ambient conditions to form the triclinic low-pressure phase containing silicon in four-, five- and sixfold coordination. The enthalpy of formation of the quench product has been measured by high-temperature oxide melt calorimetry. The value obtained from samples from a series of several synthesis experiments is ΔHf5>= (-26.32 ± 4.27) kJ mol-1r the formation from the component oxides, or ΔHf5> = (-2482.81 ± 4.59) kJ mol-1r the formation from the elements. The result is identical within experimental error to available estimates, although the previously predicted energy difference between the monoclinic and triclinic phases could not be verified.
Keywords: OXIDE MELT CALORIMETRY; FIVEFOLD COORDINATION; PENTACOORDINATE SILICON; CALCIUM DISILICATE; PHASE TRANSITION